Pendapatan dan Kesejahteraan Rumah Tangga Petani Karet di Desa Labuhan Ratu VI Kecamatan Labuhan Ratu Kabupaten Lampung Timur - Putri, Milla Selviana; Indriani, Yaktiworo; Saleh, Yuliana (Politeknik Negeri Lampung, 2024)
The majority of the people of Labuhan Ratu VI Village are engaged in rubber farming to meet their household needs. If there is a decrease in prices and a decrease in rubber production, it will affect income, income distribution and the level of household (HH) welfare, because the income received by each farmer varies. This allows the emergence of income inequality which is the beginning of poverty. This research aims to analyze the farm, HHs’ income and distribution, in addition to the welfare of rubber farmer HH. The research is conducted by survey method at Labuhan Ratu VI village, Labuhan Ratu subdistrict, East Lampung regency in January to February 2023. The research samples in this study are 58 rubber farming HHs, obtained by simple random sampling method. The data is analyzed by measuring HHs’ income and distribution while HH’s welfare is analyzed based on BPS criteria, World Bank and BKKBN. The research results showed that rubber farming income in Labuhan Ratu VI Village was profitable because the R/C value was >1. The largest HH income for rubber farmers came from rubber farming income. The distribution of rubber farmer HH income was relatively even and showed low inequality. The level of welfare of rubber farmer HHs was included in the non-poor category.